The effect of fires on some physical and chemical properties of soil (in the Qardaha region) (Latakia University Journal -Biological Sciences Series, 2022)
The fires that occurred recently, specifically on 9-10/10/2020, were painful to a great degree, after they turned the green cover in our coastal mountains into ash. The damage was not limited to the forest wealth, as agricultural soils had a large share, while the soil is the basis for the return and renewal of our forest wealth, biodiversity conservation, as well as the sustainability of agricultural production.This research aims to study the effect of fires on some physical and chemical properties of soil, as (23) sites were identified that were exposed to fire in the Qardaha area. , Soil samples were collected from the studied sites from a depth of (0-30 cm) two weeks after the fire, as well as one year after the fire from the same sites, taking into account the collection of witness samples from the sites that were not exposed to fire.The following analyzes were conducted on soil samples: percentage of organic matter, bulk density, volume distribution of individual grains, average diameter of weighted aggregates, and unburned sites were used as a control for comparison.The results of the study showed the deterioration of the soil properties as a result of the exposure of the forest system and the natural plant to fire, as the organic carbon, the proportions of clay and silt, and the average diameter of the weighted clusters decreased, while the bulk density and the proportions of sand increased significantly in the burned sites compared to the unburned. The highest percentage of decrease in the properties mentioned in the burned sites, respectively (50.33%), (35.15%), (34.2 %), (60.49%), While the highest percentage of bulk density and sand were (14.48%) and (59.59%) respectively. Where the mentioned differences were observed in the percentages of organic carbon, the average diameter of the weighted aggregates and the bulk density immediately after two weeks of the outbreak of fires, with the effects of the fire continuing after a year, but to a lesser degree, while we did not notice the differences in the proportions of clay, silt and sand until a year after the outbreak of fires.